Structural Insights into the Catalytic Cycle of a Bacterial Multidrug ABC Efflux Pump. Issue 9 (15th May 2022) - Javed, Waqas; Vallet, Sylvain; Clement, Marie-Pierre; Le Roy, Aline; Moulin, Martine; Härtlein, Michael; Breyton, Cécile; Burlet-Schiltz, Odile; Marcoux, Julien; Orelle, Cédric; Ebel, Christine; Martel, Anne; et al.
Graphical abstract: Highlights: The physical separation of the NBDs of multidrug ABC transporters is unsettled. SANS and HDX-MS have been used to address this question in BmrA. The NBD separation decreases notably from the inward- to the outward-facing state. In the ADP-bound step, the NBD separation seems larger than in the resting state. Abstract: ABC ("ATP-Binding Cassette") transporters of the type IV subfamily consist of exporters involved in the efflux of many compounds, notably those capable to confer multidrug resistance like the mammalian P-glycoprotein or the bacterial transporter BmrA. They function according to an alternating access mechanism between inward-facing (IF) and outward-facing (OF) conformations, but the extent of physical separation between the two nucleotide-binding domains (NBDs) in different states is still unsettled. Small Angle Neutron Scattering and hydrogen/deuterium exchange coupled to mass spectrometry were used to highlight different conformational states of BmrA during its ATPase cycle. In particular, mutation of the conserved Lysine residue of the Walker-A motif (K380A) captures BmrA in an ATP-bound IF conformation prior to NBD closure. While in the transition-like state induced by vanadate wild-type BmrA is mainly in an OF conformation, the transporter populates only IF conformations in either the apo state or in the presence of ADP/Mg. Importantly, in this post-hydrolytic step, distances between the two NBDs of BmrA seem to be more separated than in the apo state, but they remain shorter than the widest opening found in the related MsbA transporter. Overall, our results highlight the main steps of the catalytic cycle of a homodimeric bacterial multidrug transporter and underline structural and functional commonalities as well as oddities among the type IV subfamily of ABC transporters.